Climate-induced habitat suitability modelling for pelagic fish in European seas - Musimwa, Rutendo; Standaert, Ward; Stevens, Martha; Fernández Bejarano, Salvador Jesus; Muñiz, Carlota; Debusschere, Elisabeth; Pint, Steven; Everaert, Gert (Frontiers in Marine Science, 2025)
Pelagic fish species, including Clupea harengus (Atlantic herring), Scomber scombrus (Atlantic mackerel) and Dicentrarchus labrax (European seabass), are integral to the ecological stability of European marine ecosystems. This study employs a mechanistic niche modelling approach to predict the distribution of these key pelagic species in European seas and to assess the impact of predicted changes in climate conditions on their suitable habitat range. By using fuzzy logic principles and mathematical descriptions of species’ niches, we analysed responses to changing temperature and salinity using climate prediction data from six Shared Socioeconomic Pathways (SSP) scenarios, predicting habitat suitability from the present (2010-2019) until 2100. Under the worst-case temperature climate scenario, all three species exhibited a consistent northward shift of suitable habitats by 2100. Specifically, the suitable habitat for C. harengus, S. scombrus and D. labrax is projected to shift approximately 638 km, 799 km and 13 km north, respectively. The independent contributions of temperature and salinity indicate a distinction in habitat suitability between northern European waters and the Mediterranean Sea, with higher suitability scores in the north. For example, by 2100, the habitat suitability index for non-spawning Atlantic herring in the North Atlantic Ocean is projected to be 0.63 ± 0.3 under SSP5-8.5 compared to the current habitat suitability index of 0.49 ± 0.36, while the index is projected to 0.02 ± 0.003 in the Mediterranean Sea-Western Basin with the current index at 0.01 ± 0.03. These findings suggest that northern latitudes, encompassing regions such as the North Sea and the Baltic Sea currently offer more favorable conditions compared to the lower latitudes of the Mediterranean region. The study’s findings should guide policy decisions in environmental and marine resource management, ensuring interventions are based on up-to-date information and account for anticipated climate change impacts.